PENERAPAN STRATEGI PEMBELAJARAN METAKOGNITIF TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS XI IPS SMA NEGERI 1 TALAMAU KABUPATEN PASAMAN BARAT - Melia Roza (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2017)
Abstract : This study aims to reveal the students' mathematical reasoning abilities after being given treatment metacognitive learning strategies. The research is a pre-experimental study design Randomized Control Group Only Design. Sampling was conducted using random sampling techniques so chosen as an experimental class is a class XI IPS 2 and a control class is the class XI IPS 1. The research instrument is a student activity observation sheet and test students' mathematical reasoning abilities. Data analysis was performed using the t test with significance level ? = 0.05. Based on t test was done, obtained t = 1.9155 and table = 1.69 it is seen that thitung> ttabel means to reject H0 and accept H1. So it can be concluded that the mathematical reasoning skills students learn better metacognitive learning strategies than students who studied with conventional strategies in class XI IPS SMAN 1 Talamau West Pasaman academic year 2016/2017